In situ investigation of halide incorporation into perovskite solar cells. (10th July 2017) - Aguiar, Jeffery A.; Alkurd, Nooraldeen R.; Wozny, Sarah; Patel, Maulik K.; Yang, Mengjin; Zhou, Weilie; Al-Jassim, Mowafak; Holesinger, Terry G.; Zhu, Kai; Berry, Joseph J.
Abstract: Abstract : Here we report on the material chemistry following crystallization in the presence of water vapor of chlorinated formamidinium lead-triiodide (NH2 CH = NH2 PbI3−x Clx ) perovskite films. We found in-situ exposure to water vapor reduces, or possibly eliminates, the retention of chlorine (Cl) inside NH2 CH = NH2 PbI3− x Cl x crystals. There is a strong tendency toward Cl volatility, which indicates the sensitivity of these materials for their integration into solar cells. The requisite for additional efforts focused on the mitigation of water vapor is reported. Based on the in situ results, hot casting (<100 °C) in dry conditions demonstrates improved film coverage and Cl retention with efficiencies reaching 12.07%.